2017
DOI: 10.1002/apj.2162
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on coal water slurries prepared from coal gasification wastewater

Abstract: Coal gasification wastewater (CGW) contains high concentrations of pollutants and varying chemical components and thus is difficult to treat. CGW slurry (CGWS), which is prepared by blending coal, CGW, and additives, is a new wastewater utilization technology that can be used to efficiently and conveniently treat CGW. This work mainly investigated the slurryability, rheology, stability, and combustion properties of CGWS prepared from Shenhua and Yima coals. Results showed that (a) the maximum solid loading of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Stability was evaluated through the water separation ratio (WSR). The determination process is explained in detail in refs , , and .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stability was evaluated through the water separation ratio (WSR). The determination process is explained in detail in refs , , and .…”
Section: Methodsmentioning
confidence: 99%
“…The aforementioned studies demonstrate the feasibility of coal–organic wastewater–slurry. However, studies on the preparation of coal–coal gasification wastewater–slurry are rare, and information regarding the effects of various components of coal gasification wastewater on the slurrying property is insufficient, i.e., the co-slurrying mechanisms of coal gasification wastewater and coal remain unclear. The present study focused on the viscosity, rheological property, and stability of coal–coal gasification wastewater–slurry.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the improvement of environmental protection requirements and popularization of the concept of sustainable development, the technology of preparing CWS from different types of wastewater has received widespread attention as a new and efficient wastewater treatment technology. The preparation of coal wastewater slurry (CWWS) not only saves fresh water but also efficiently treats and recycles high‐concentration wastewater that is difficult to biochemically process, which is a clean coal technology with both economic and environmental benefits 12 . Makarov et al verified that acidic and alkaline industrial wastewater, and wastewater containing alcohol as a dispersion medium can all be used for CWS preparation 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of coal wastewater slurry (CWWS) not only saves fresh water but also efficiently treats and recycles high-concentration wastewater that is difficult to biochemically process, which is a clean coal technology with both economic and environmental benefits. 12 Makarov et al verified that acidic and alkaline industrial wastewater, and wastewater containing alcohol as a dispersion medium can all be used for CWS preparation. 13 Wang et al used coking wastewater to prepare CWS and indicated that the maximum slurrying concentration for coal coking wastewater slurry is increased by 0.8% compared with ordinary CWS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the production processes of the coal chemical industry not only consume freshwater resources but also produce a large amount of wastewater, which contains a large number of complex toxic and hazardous substances and difficult-to-treat compounds. [2] For example, wastewater generated in the production of semicoke contains more than 300 organic and inorganic pollutants.…”
mentioning
confidence: 99%